Analysis Of Taman Raja Batu Madina Tourist Attractions On The Welfare Of Local Communities In The Tourist Area Of Mandailing Natal Regency - Wasila; Anggia Ramadhan; Rahmad Sembiring (International Journal of Management, Economic and Accounting, 2024)
The construction of the Batu Madina King Park tourist attraction in the Perbaungan Mandailing Natal area is expected to improve the welfare of the surrounding community. This study aims to analyze the influence of public facilities, visitor satisfaction, and tourist attraction on the increase in direct income in Perbaungan Aek Godang Mandailing Natal village. Methods This study uses the causal method, to see how independent variables directly affect dependent variables through experiments. This study uses a questionnaire research instrument by distributing direct questions to respondents to get accurate data using the Liker scale. The hypothesis test uses multiple linear regression with the aim of finding out the direction of the interaction of the independent variable to the dependent variable. The results of the study show that Public Facilities, Visitor Satisfaction, and Tourism Attractions are able to affect Income in Perbaungan Aek Godang Mandailing Natal village. Public Facilities (x1), Visitor Satisfaction (x2), Tourist Attractions (x3) together or simultaneously have a sinisterly effect on revenue (Y)